Development of high microwave-absorptive bifunctional graphene oxide-based catalyst for biodiesel production - Loy, A.C.M. (2019)
A novel heterogeneous bi-functional catalyst namely silicon carbide/sodium hydroxide-graphene oxide (SiC/NaOH-GO) was successfully developed and characterized using fourier transform infrared spectroscopy (FT-IR), thermogravimetry analysis (TGA), scanning electron microscope (SEM), energy disperse X-ray analysis (EDX), BrunauerâEmmettâTeller analysis (BET), X-ray diffraction (XRD), carbon dioxide temperature programmed-desorption of carbon dioxide (CO 2 -TPD) and ammonia temperature programmed-desorption (NH 3 -TPD). The catalyst was applied in microwave-assisted transesterification and esterification of binary model feedstock (rapeseed oil and oleic acid) containing 20 free fatty acid (FFA) and optimized using respond surface methodology (RSM) based on centre composite design. The study revealed that the optimum reaction conditions were 13:1 wt ratio of SiC/NaOH to GO, 5 wt of catalyst loading, reaction temperature of 65 Â°C and 6 min reaction time to attain 96 of yield of transesterification and 92 of yield of esterification. Then, the optimized catalyst (13:1 wt ratio of SiC/NaOH) was applied in Chlorella vulgaris lipid with high free fatty acid content (26) to further confirmed the ability of converting triglycerides and free fatty acid (FFA) to biodiesel simultaneously. The study revealed that 92 of FFA of microalgae lipid was converted and 81 of fatty acid methyl ester content (FAME) was attained under the optimum conditions of methanol to lipid molar ratio of 48, 5 min reaction time, 4 wt catalyst and reaction temperature of 85 Â°C. Â© 2018 Elsevier Ltd